Hubungan status gizi, konsumsi fast food, tingkat stres dengan kejadian hipertensi di Kota Bengkulu - Sela Maria; Emy Yuliantini; Kamsiah Kamsiah (Poltekkes Kemenkes Aceh, 2026)
Background: This study was motivated by the high incidence of hypertension in the Pasar Ikan Health Center area of Bengkulu City. Lifestyle changes, such as increased fast-food consumption and high stress levels, are suspected to be the main risk factors contributing to the incidence of hypertension in the local community.Objectives: This study aimed to determine the relationship between nutritional status, fast-food consumption, stress levels, and the incidence of hypertension at the Pasar Ikan Community Health Center in Bengkulu City in 2025.Methods: An observational study with a cross-sectional design was conducted at the Fish Market Health Center in Bengkulu City from April to May 2025. The sample calculation results were obtained using accidental sampling of visitors aged 20–45 years, and 84 respondents who met the criteria were selected. Data were collected through nutritional status measurements, completion of questionnaires using the Food Frequency Questionnaire (FFQ) and Perceived Stress Scale-10 (PSS-10), and statistical analysis using the chi-square test.Results: Most respondents were aged 36–45 years (83.3% female and 16.7% male). Based on the results of statistical testing, nutritional status and fast-food consumption were not significantly associated with the incidence of hypertension, as indicated by p-values of 0.262 (nutritional status), 0.498 (fast food), and 0.001 (stress level), respectively. A relationship between stress levels and the incidence of hypertension in the working population of the Pasar Ikan Community Health Center, Bengkulu City was identified (p = 0.001).Conclusion: Nutritional status and fast food consumption were not associated with hypertension. However, stress levels were associated with hypertension in the Pasar Ikan Community Health Center in Bengkulu City.